2008
DOI: 10.1007/s10157-008-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria and decreased body mass index as a significant risk factor in developing end-stage renal disease

Abstract: The findings of the present study suggest that a DeltaBMI is an independent risk factor for the incidence of ESRD, especially for those with proteinuria. The reasons for the BMI change were not recorded in this study. Unintentional weight loss, however, might warrant evaluation for the presence or progression of chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The target population of CKD screening could be the general population of community or high‐risk groups. At present, the general population were mostly used as the research object, such as the Third National Health and Nutrition Examination Survey (NHANES III) of the USA, the Australian AusDiab study, the Norwegian Nord–Trøndelag Health Study (HUNT) study, Japan's Okinawa screening program and Hong Kong's SHARE 13–17 in China, while the study object of KEEP US was high‐risk groups, including the patients with hypertension, diabetes or the first‐level relatives of people with high BP, diabetes and kidney disease 18,19 . Some scholars believed that the latter had a better direction and cost–benefit ratio, 20 and choosing the subjects who had known risk factors for susceptibility to CKD could find relatively high prevalence and screening rate, and could help to find more asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The target population of CKD screening could be the general population of community or high‐risk groups. At present, the general population were mostly used as the research object, such as the Third National Health and Nutrition Examination Survey (NHANES III) of the USA, the Australian AusDiab study, the Norwegian Nord–Trøndelag Health Study (HUNT) study, Japan's Okinawa screening program and Hong Kong's SHARE 13–17 in China, while the study object of KEEP US was high‐risk groups, including the patients with hypertension, diabetes or the first‐level relatives of people with high BP, diabetes and kidney disease 18,19 . Some scholars believed that the latter had a better direction and cost–benefit ratio, 20 and choosing the subjects who had known risk factors for susceptibility to CKD could find relatively high prevalence and screening rate, and could help to find more asymptomatic patients.…”
Section: Discussionmentioning
confidence: 99%
“…The participants from the semiurban communities had a higher mean weight/BMI which has been shown in some populations to protect against CKD. 12 The prevalence of markers of CKD (proteinuria and/or hematuria) in this study was 19%. Of the number that had hematuria, 66.1% were females, this in part, could be due to the higher prevalence of urinary tract infections in women.…”
Section: Correlations and Multiple Regression Analysismentioning
confidence: 97%
“…Other predictors in Table 1 are also statistically significant, but the clinical significance is less than that of proteinuria and hypertension 8–13 . Effects of obesity on CKD and ESRD were complex and we observed that the decrease in body mass index was a risk factor for developing CKD 14 and ESRD 15 . Low glomerular filtration rate (GFR) per se was not significant, unless otherwise associated with proteinuria 16 .…”
Section: Predictors Of Esrd Among Screened Subjects (Table 1)mentioning
confidence: 87%
“…[8][9][10][11][12][13] Effects of obesity on CKD and ESRD were complex and we observed that the decrease in body mass index was a risk factor for developing CKD 14 and ESRD. 15 Low glomerular filtration rate (GFR) per se was not significant, unless otherwise associated with proteinuria. 16 The annual incidence of ESRD was approximately 1% in those with dip-stick 3+ and over and renal biopsy recipients.…”
Section: Predictors Of Esrd Among Screened Subjectsmentioning
confidence: 99%